2007
DOI: 10.1002/hon.819
|View full text |Cite
|
Sign up to set email alerts
|

Patients with bisphosphonates‐associated osteonecrosis of the jaw have reduced circulating endothelial cells

Abstract: Osteonecrosis of the jaws (ONJ) associated with the use of bisphosphonates is a newly described entity. To elucidate the mechanism leading to ONJ and to test the hypothesis that in patients with ONJ the bisphosphonates may interfere with endothelial cell proliferation, using flow cytometric analysis we evaluated the number of circulating endothelial progenitor cells (EPCs) and circulating endothelial cells (CECs) in eight patients with bisphosphonate treatment and osteonecrosis, eight multiple myeloma (MM) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…This is an unexpected finding as in previous studies we demonstrated the possibility that BPs could have a suppressive effect on angiogenesis (4,38). However, BPs could exert a different action on bone and mucosal tissue.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is an unexpected finding as in previous studies we demonstrated the possibility that BPs could have a suppressive effect on angiogenesis (4,38). However, BPs could exert a different action on bone and mucosal tissue.…”
Section: Discussionsupporting
confidence: 69%
“…Several theories have been proposed regarding the pathoetiology of ONJ, e.g. that necrosis is related to an over-suppression of bone turnover by BPs (2) or that BPs decrease angiogenesis (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Our data are different from results presented in a previous work [14] which demonstrated that there is an increase in CECs in patients with myeloma. This discrepancy could be due to the different characteristics of the patients studied.…”
Section: Discussioncontrasting
confidence: 57%
“…In a previous work using flow-cytometric analysis, we demonstrated a decrease in circulating endothelial progenitor cells (EPCs) in patients with BP ONJ compared to control subjects [14]. …”
Section: Introductionmentioning
confidence: 99%
“…The antiangiogenic activity of NBPs has been suggested as one of the main determinants of ONJ onset. [42][43][44] A recent review reported a wideranging ONJ incidence from 0% to 27.5%, relevant to individuals exposed to intravenous NBP, with a mean incidence of 7%. 45 Table 1 Continued This retrospective exploratory study was aimed at describing the occurrence and the nature of ONJ associated with the use of NBP and targeted agents in RCC patients.…”
Section: Discussionmentioning
confidence: 97%